Lipoxin A4 yields an electrophilic 15-oxo metabolite that mediates FPR2 receptor-independent anti-inflammatory signaling - Adolf Koudelka; Gregory J. Buchan; Veronika Cechova; James P. O’Brien; Emily R. Stevenson; Crystal E. Uvalle; Heng Liu; Steven R. Woodcock; Steven J. Mullett; Cheng Zhang; Bruce A. Freeman; Stacy L. Gelhaus (Journal of Lipid Research)
The enzymatic oxidation of arachidonic acid is proposed to yield trihydroxytetraene species (termed lipoxins) that resolve inflammation via ligand activation of the formyl peptide receptor, FPR2. While cell and murine models activate signaling responses to synthetic lipoxins, primarily lipoxin A4 (LXA4), there are expanding concerns about the reported biological formation, detection, and signaling mechanisms ascribed to LXA4 and related di- and tri-hydroxy ω-6 and ω-3 fatty acids. The generation and signaling actions of LXA4 and its primary 15-oxo metabolite were assessed in control, lipopolysaccharide-activated, and arachidonic acid-supplemented RAW264.7 and bone marrow-derived macrophages. Despite the expression of catalytically active enzymes required for LXA4 synthesis, both LXA4 and its 15-oxo-LXA4 metabolite were undetectable in all conditions. Moreover, synthetic LXA4 and the membrane-permeable 15-oxo-LXA4 methyl ester, which rapidly de-esterified to 15-oxo-LXA4, displayed no ligand activity for the putative LXA4 receptor FPR2. Alternatively, 15-oxo-LXA4, an electrophilic α,β-unsaturated ketone, alkylates nucleophilic amino acids and can modulate redox-sensitive transcriptional regulatory protein and enzyme function. 15-oxo-LXA4 activated nuclear factor (erythroid related factor 2)-like 2-regulated expression of anti-inflammatory and repair genes and inhibited NF-κB-regulated pro-inflammatory mediator expression. Synthetic LXA4 showed no impact on these macrophage anti-inflammatory and repair responses. In summary, these data show an absence of macrophage LXA4 formation and receptor-mediated signaling actions of synthetic LXA4. Rather, if present in sufficient concentrations, LXA4 and other mono- and poly-hydroxylated unsaturated fatty acids synthesized by macrophages would be readily oxidized to electrophilic α,β-unsaturated ketone products that modulate the redox-sensitive cysteine proteome via G-protein coupled receptor-independent mechanisms.